Dengue incidence studies a national study on precipitation, gross regional domestic product, population and dengue incidence in the Philippines - Morales, Dianne D.; Alviola, Pedro A. IV. (Davao City School of Management, University of the Philippines Mindanao, 2016)
Dengue Fever and Dengue Hemorrhagic Fever have been considered global health threats which are endemic in tropical, sub-tropical, and Southeast Asian countries. It affects mostly children and is one of the main causes of child mortality in the Philippines. Based on previous studies, the increase in dengue incidences is associated with temperature, precipitation, and urbanization factors. However, some studies contradict these findings and have found no sufficient evidence to prove that these factors are associated with the increase in dengue counts. In addition, studies conducted in the Philippines have been site-specific only. Hence, this study focused on determining the significant factors affecting dengue incidences and computing the range of precipitation which increases it, in every region in the Philippines. Using a Panel Regression Econometric Model, the annual total of dengue counts, GRDP, precipitation, and population from years 2008-2012 were utilized. In both non-clustered and boostrap model, precipitation in the random effects and fixed effects models were statistically significant. The Gross Regional Domestic Product (GRDP) has also shown significance in both panel regressions: pooled, random effects, and fixed effects; and bootstrap: fixed effects only. The population has shown statistical significance in the non-cluster: pooled and random effects models. The range of precipitation which heightens dengue counts were also computed and yielded a result of 5096.62 mm to positive infinity annually for the fixed effects model. This study concludes that the increase in dengue incidences is affected by precipitation and urbanization. Thus, monitoring precipitation levels and improving dengue alleviation policies (e.g. waste management) are important to address this issue. More seminars about dengue awareness should be conducted to alleviate dengue and lessen child mortality rates. Also, investing in water drainage systems will alleviate the problem of dengue incidences, especially in urban areas.
Thesis (BS Agribusiness Economics)-- University of the Philippines Mindanao, June 2016